DMPA-SC self-injection experiences of clients and providers in Uganda: the role of community health workers in reproductive self-care service delivery - Jane Cover; Allen Namagembe; Barbara Kunihira; Cecilia Nantume; Andrew Secor; Fiona Walugembe (BMC Women's Health)
Abstract Accelerating task sharing for family planning and contraceptive self-care can minimize the impact of a projected shortage of 18 million health care workers by 2030. This cross-sectional study assessed the potential of community health workers (CHWs) to offer family planning counseling and self-injection training comparable in quality to that provided by clinic health workers. The study employed exit interviews with 240 injectable clients and 80 of the providers who conducted their counseling, from 43 purposively selected public sector clinics across eight districts of Uganda. The study examined the feasibility, acceptability, and quality of contraceptive service delivery, including self-injection training for women interested in self-care. The study also measured awareness and interest in self-injection among women and assessed provider receptivity to offering self-injection. Data was analyzed using STATA 14.2, using chi square and t-tests to measure for any bivariate significant differences at conventional significance levels for two-sided tests (p < .05). Results from interviews with injectable clients revealed a high level of interest in self-injection, ranging from 48 to 80% depending on the metric used. With respect to the quality of family planning counseling, interviews with clients indicate that CHWs provide a higher quality of care than that offered by their clinic-based counterparts, whether measured by the method information index plus (MII +) or the Quality of Contraceptive Counseling (QCC) scale. In terms of self-injection training, CHWs were significantly more likely to conduct individual training, ensure private time with the client (if trained in a group), show the client a job aid, and advise on disposal. In terms of receptivity to self-injection, both groups of providers expressed favorable views in general, though a substantial share would place restrictions on who can self-inject, limiting access for covert users (41%), adolescents (49%), and new users (58%). CHWs self-reported as better able to accommodate the time required for high quality family planning counseling and self-injection training. The findings from this study should reassure stakeholders that, when provided with appropriate, competency-based training and supervision, CHWs can help to fill a looming human resource shortfall, reinforcing family planning service delivery while reaching women who face profound geographic access challenges.